2015
DOI: 10.1016/j.jjie.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Childcare availability, household structure, and maternal employment

Abstract: We estimate the causal effects of childcare availability on the maternal employment rate using prefecture panel data constructed from the Japanese quinquennial census 1990-2010. We depart from previous contributions by controlling for prefecture fixed effects, without which the estimates can be severely biased upward. We find that the treatment effect is heterogeneous: the employment rate of mothers in nuclear households increases with childcare availability, while that of mothers in three-generation household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 20 publications
1
55
3
Order By: Relevance
“…Our finding of the significant effects of day care contrasts with the recent study of Asai et al (2015) who challenged many earlier studies on the effect of childcare on maternal labor supply by stating that their prefectural fixed effects model suggested that childcare provision was only a substitute for the informal care provided by grandparents and that it did not increase maternal employment in three-generation households, even though the effect was significant in nuclear households. Asai et al use prefectural Census data aggregated by family type that spans the period 1990-2010.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding of the significant effects of day care contrasts with the recent study of Asai et al (2015) who challenged many earlier studies on the effect of childcare on maternal labor supply by stating that their prefectural fixed effects model suggested that childcare provision was only a substitute for the informal care provided by grandparents and that it did not increase maternal employment in three-generation households, even though the effect was significant in nuclear households. Asai et al use prefectural Census data aggregated by family type that spans the period 1990-2010.…”
contrasting
confidence: 99%
“…11 Our measurement approach departs from Asai et al (2015) or Unayama (2011), who use the number of accredited day care places for 0-6-year-old divided by the number of children in that age for the relevant prefecture. The present paper uses an index based on 2-year-olds for two reasons.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existing evidence for the effectiveness of childcare reforms on mothers' labor supply is mixed across time and countries. Indeed, many papers find that the effect of childcare on maternal labor supply is small and/or statistically insignificant (see Lundin, Mörk, and Öckert (2008), Cascio (2009), Goux and Maurin (2010), Fitzpatrick (2010Fitzpatrick ( , 2012, Havnes and Mogstad (2011) and Asai, Kambayashi, and Yamaguchi (2015)). …”
Section: Introductionmentioning
confidence: 99%
“…Since the data from these surveys provide limited information regarding the caregiving activities of middle-aged people, Kondo (2017) addresses this issue by considering the availability of long-term care facilities in prefectures and medical districts to be a proxy for an individual's unlikelihood of caring for his/her frail elderly parents. This method is similar to that of Asai et al (2015) who use prefecture-level data to study the relationship between the capacity of child-care centers and the labor market participation of mothers. Kondo (2017) concludes that the availability of long-term care facilities is unrelated to the labor market participation of middle-aged men and women.…”
mentioning
confidence: 99%